Phytochemical Identification and Antioxidant Activity Test of Acetone Extract of Celery Leaves (Apium graveolens L.) Using the DPPH (2,2-diphenyl-1-picrylhydrazyl) Method - Riska Auliannisa; Gervacia Jenny; Herlinda Djohan (MEDICA (International Medical Scientific Journal), 2024)
Free radicals are formed in the body through oxidation processes and cell combustion during breathing, metabolism, excessive physical activity, as well as exposure to external pollution. Antioxidants play an important role in protecting the body from oxidative damage. Celery leaves (Apium graveolens L.), which are rich in flavonoid compounds, have the potential to be a natural source of antioxidants. This study aims to identify the secondary metabolite content and measure the antioxidant activity of acetone extract of celery leaves based on IC50 values using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The study uses a quasi-experimental design with purposive sampling techniques. The antioxidant activity of acetone extract of celery leaves at concentrations of 30 ppm, 50 ppm, 70 ppm, and 90 ppm was tested using a UV-VIS spectrophotometer at a wavelength of 516 nm. The results showed the presence of secondary metabolite compounds such as alkaloids, flavonoids, phenols, triterpenoids, saponins, and tannins in the acetone extract of celery leaves. The IC50 value of the acetone extract of celery leaves was 115.09490 ppm, indicating moderate antioxidant activity (IC50 value between 100–250 ppm). These findings conclude that acetone extract of celery leaves has potential to be used as a natural antioxidant source.